Analisis Daya Dukung Lahan sebagai Pengembangan Fasilitas Perkotaan Kecamatan Mpunda Kota Bima Tahun 2015 – 2035 - Rasyid Ridha; Nyoman Utari Vipriyanti; IGN. Alit Wiswasta (Department of Urban and Regional Planning, Diponegoro University, 2016)
This study is based on the phenomenon of development in Bima City and affects the physical condition of the region and not evenly of facilities distribution. So that, it is necessary to analyze the carrying capacity of urban area facilities development in Mpunda District, Bima City 2015-2035. The study aims to determine the carrying capacity of Mpunda District to provide a suitable area for the development of urban facilities. The analysis uses both qualitative and quantitative description in the Mpunda District to describe the general overview of geographic distribution facilities. The analytical method used is based on Public Works Minister Regulation No.20/PRT/M/2007 about Technical Guidelines for Physical & Environmental analysis. Analysis facility needs in planning is always based on the development trend of the population. The calculation for projecting the need facilities is based on SNI 03-1733-2004 about Procedures for Environmental Planning about Housing Design in City and Need of Environmental Facilities. The analysis results of the carrying capacity of the urban area facilities development in Mpunda District is by establishing the protected areas based on the physical condition especially for class 4 of land capability which have the lowest ability with the land cover ratio in 2035 is 0%. Controlling as the functions of the buffer zone must be done for class 3 of land capability. The development land is directed for the class 1 and class 2 as the cultivation land. There is land development, which is 20%. For the cultivation of land or land suitable for development land directed to land capability and land capability class 1 class 2. The ratio of class 1 land coverage area in 2035 has reached the maximum land cover ratio, i.e. 70%. While the ratio of class 2 land coverage area in 2035, i.e. 49% of from the 50% maximum of land cover ratio.